Leadership Style and Its Impact on Employee Performance - Bela Ayu Pratiwi; Hariati Hariati (PINISI Discretion Review, 2026)
This study aims to determine whether there is an influence of leadership style on employee performance in Kembang Janggut District, Kutai Kartanegara Regency. This study uses a quantitative research method with a sample of 43 people by collecting data through direct observation and filling out questionnaires measured using a Likert scale. To analyze the data, a simple linear regression test was used with a significance level of 5% through the SPSS version 30 application. The results of data processing and hypothesis testing empirically prove that Employee Performance is significantly influenced by Leadership Style. This conclusion is based on the results of the t test which shows the t count value exceeds the t table (8.112 > 2.019) with a valid significance value (0.001 < 0.05). The causal relationship between these variables is described through the regression formula Y = 11301.050 + 0.481X. Through testing the coefficient of determination, an R Square value of 0.616 was obtained. These results indicate that the contribution or contribution of the influence of the Leadership Style variable (X) on Employee Performance (Y) is 61.6%. The remaining 38.4% is explained by variables outside the focus of this study. Recommendations from this study include increasing the authority given to employees in carrying out their duties and making independent decisions so that they are not dependent on the physical presence of the sub-district head, and introducing a reward system for employees to transform employee integrity into professional commitment to improve public service delivery for the people of Kembang Janggut Sub-district.